2021
DOI: 10.1530/joe-21-0037
|View full text |Cite
|
Sign up to set email alerts
|

Leptin system loss of function in the absence of obesity in zebrafish

Abstract: The leptin system plays a crucial role in the regulation of appetite and energy homeostasis in vertebrates. While the phenotype of morbid obesity due to leptin or leptin receptor (lepr) loss of function is well established in mammals, evidence in fish is controversial, questioning the role of leptin as the vertebrate adipostat. Here we report on 3 lepr loss of function (lof) and one leptin loss of function allele in zebrafish. In order to demonstrate that the lepr lof alleles cannot transduce a leptin signal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…With regard to leptin, zebrafish have two major leptin genes: lepa and lepb, and one leptin receptor gene lepr [19,20]. Previously, the obesity phenotype has been observed in a lepa-deficient adult zebrafish [21], however in another study, the obesity phenotype was not consistently observed in lepa or lepr deficient zebrafish [22]. Recently, Kamstra et al have shown that overfeeding elicits elevated body weight in both lepr and lepa deficient zebrafish as compared to control [23].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to leptin, zebrafish have two major leptin genes: lepa and lepb, and one leptin receptor gene lepr [19,20]. Previously, the obesity phenotype has been observed in a lepa-deficient adult zebrafish [21], however in another study, the obesity phenotype was not consistently observed in lepa or lepr deficient zebrafish [22]. Recently, Kamstra et al have shown that overfeeding elicits elevated body weight in both lepr and lepa deficient zebrafish as compared to control [23].…”
Section: Introductionmentioning
confidence: 99%